Tell Me What You See: An Arts-Based Health Education Program for Youth. - Edmondson, Bonnie (Health Promotion Practice, 2021)
A cross-sector collaboration among a community-based organization, a prison arts program, and state departments of Public Health, Education, and Correction was established to address critical health education prevention efforts for at-risk high school-aged youth. The Tell Me What You See initiative utilizes artwork and poetry created by incarcerated youth to promote sexually transmitted disease (STD), HIV, and hepatitis prevention with students in public high schools and juvenile justice facilities. This innovative intervention integrates functional health knowledge and skills-based education through an art-based interdisciplinary approach reaching various populations of youth in multiple settings across a state. Evaluation results indicated that the materials effectively engage youth and open up a critical dialogue among peers and adults by addressing the role personal behavior can have in the prevention of STDs, hepatitis, and HIV. Lessons learned and recommendations are provided., (C)2021Sage Publications
Keywords: Adolescent; Adult; Child; Educational Status; HIV/AIDS; Health Education; Health Promotion; Humans; STDs; Schools; Sexually Transmitted Diseases; adolescent; adolescent health; adult; arts; arts in public health; arts-based education; behavior change; child; community organization; creative arts; dept.hms; educational status; health education; health promotion; hepatitis; human; incarcerated youth; juvenile justice; partnerships; peer-reviewed; public health; school; school health; sexually transmitted disease